Pavement recycling: an environmentally sustainable rehabilitation alternative - Oliveira, Joel (2007)
The preservation of environment by reducing the use of material and natural resources together with important economic savings have led pavement recycling to be a prime solution for pavement maintenance/rehabilitation. It is based on sustainable development, by reusing materials reclaimed from the pavements and reducing the disposal of asphalt materials. The present paper focuses on the analysis of a heavily trafficked urban road rehabilitation project. The original pavement design did not take into account the current traffic levels which are considerably above the initial values. The pavement was reaching failure in several areas and needed urgent measures to avoid complete failure. The pavement condition was a result of lack of structural strength and a deficient drainage. A semi-rigid pavement structure was proposed in order to improve the bearing capacity of the pavement and minimize the maintenance operations in the future. The operations involved cold “in situ” recycling of part of the existing bituminous layers and the top part of the granular layers with the addition of cement, and the overlay with new bituminous mixtures incorporating a significant percentage of materials reclaimed from the surface course of the same pavement. This solution allowed the maintenance of the pavement level (without the need for footpath reconstruction) and minimized the use of new materials, contributing towards a sustainable development.